2018
DOI: 10.3389/fmicb.2018.01953
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus plantarum Promotes Intestinal Barrier Function by Strengthening the Epithelium and Modulating Gut Microbiota

Abstract: Weaning disturbs the intestinal barrier function and increases the risk of infection in piglets. Probiotics exert beneficial health effects, mainly by reinforcing the intestinal epithelium and modulating the gut microbiota. However, the mechanisms of action, and especially, the specific regulatory effects of modulated microbiota by probiotics on the intestinal epithelium have not yet been elucidated. The present study aimed to decipher the protective effects of the probiotic Lactobacillus plantarum strain ZLP0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
229
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(244 citation statements)
references
References 57 publications
9
229
0
6
Order By: Relevance
“…Studies on L. plantarum as feed additives in another species showed improvement of gut barrier function accompanied by a better gut environment. Post-weaning piglets received L. plantarum in the diet had improvement in the regulation of tight junction proteins (claudin-1, occludin and zona-occluden-1 (ZO-1)) concurrently with the strengthening of epithelium and modulating gut microbiota [55]. In suckling piglets, L. plantarum administration in the diet upregulated the jejunal OCLD, ileal ZO-1 and jejunal and the ileum of porcine B-defensin with an improvement of intestinal morphology and increment of relative abundance of phyla Firmicutes and Actinobacteria and genus Lactobacillus [56].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on L. plantarum as feed additives in another species showed improvement of gut barrier function accompanied by a better gut environment. Post-weaning piglets received L. plantarum in the diet had improvement in the regulation of tight junction proteins (claudin-1, occludin and zona-occluden-1 (ZO-1)) concurrently with the strengthening of epithelium and modulating gut microbiota [55]. In suckling piglets, L. plantarum administration in the diet upregulated the jejunal OCLD, ileal ZO-1 and jejunal and the ileum of porcine B-defensin with an improvement of intestinal morphology and increment of relative abundance of phyla Firmicutes and Actinobacteria and genus Lactobacillus [56].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps these changes in miRNA levels also play a role in the alleviation of diseases (112). As another example, Lactobacillus plantarum ZLP001 impacts the composition of the intestinal microflora, and increases the abundance of butyrate-producing bacteria such as Anaerotruncus and Faecalibacterium in the 30-day trial (113). Meanwhile, in terms of immune regulation, the strain downregulates production of proinflammatory cytokines, including IL-6, IL-8, and TNF-α, and increases levels of host defense peptides pBD2 and PG1-5.…”
Section: Intestinal Flora Can Be Used To Reconstruct Regional Immunitmentioning
confidence: 99%
“…Meanwhile, in terms of immune regulation, the strain downregulates production of proinflammatory cytokines, including IL-6, IL-8, and TNF-α, and increases levels of host defense peptides pBD2 and PG1-5. Ultimately, L. plantarum ZLP001 strengthens the intestinal barrier by improving the epithelial defense function and regulating the intestinal microbiota, which reduces the risk of infection (113).…”
Section: Intestinal Flora Can Be Used To Reconstruct Regional Immunitmentioning
confidence: 99%
“…Lactobacillus plantarum is considered an excellent probiotic in the gastrointestinal tracts of humans and animals and performs important probiotic actions, such as inhibiting Escherichia coli ‐induced intestinal permeability, reducing the incidence of Clostridium difficile , alleviating oxidative damage to the liver, improving growth performance and increasing intestinal immunity and anti‐inflammatory properties (de Vries, Vaughan, Kleerebezem, & de Vos, ; Dudzicz, Kujawa‐Szewieczek, Kwiecien, Wiecek, & Adamczak, ; Fak, Ahrne, Molin, Jeppsson, & Westrom, ; Herías et al, ; Khanian, Karimi‐Torshizi, & Allameh, ; Malik et al, ; Wullt, Johansson Hagslatt, Odenholt, & Berggren, ). Researches have shown that oral administration of L. plantarum can improve the immune responses and enhance the intestinal barrier function of weaning piglets (Wang, Ji, et al, ; Yang, Jiang, Zheng, Wang, & Yang, ). Diet with L. plantarum ‐fermented wheat also can improve the apparent total tract digestibility of nutrients and energy, nitrogen retention, and energy content of weaned piglets (Koo, Bustamante‐García, & Nyachoti, ).…”
Section: Introductionmentioning
confidence: 99%